INTRACERVICAL MISOPROSTOL EFFECTIVENESS IN ABORTION AND ORAL FRUSTRATED AND DEATH FETAL - Rojas, Estanislao (2015)
OBJECTIVE: To determine the dose and best rute of administration of misoprostol in the uterine evacuation of both missed abortion and fetal death. MATERIAL AND METHODS: Between November 1997 and May 1999 we evaluated 95 women with missed abortion and fetal death. We compared the effectiveness of oral misoprostol 400 mg combined with intracervical misoprostol 200 mg. RESULTS: In 95 selected patients divided in two groups of missed abortion (75 patients) and fetal death patients the best dose was the oral 400 mg with 200 mg intracervical with a latency period of 4-5 hours and 5-6 hours, respectively. CONCLUSIÓN: Oral m isoprostol 400 mg combined with intracervical 200 mg is able to diminish significantly the time of latency in both study groups.